2009
DOI: 10.4103/0256-4947.51801
|View full text |Cite
|
Sign up to set email alerts
|

Transient osteoporosis of the hip

Abstract: Transient osteoporosis of the hip is an uncommon cause of hip pain, mostly affecting healthy middle-aged men and also women in the third trimester of pregnancy. We present a case of transient osteoporosis of the hip in a 33-year-old non-pregnant female patient. This case highlights the importance of considering a diagnosis of transient osteoporosis of the hip in patients who present with hip pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Out of the 12 patients diagnosed as avascular necrosis, the disease was bilateral in [6] 50% of patients Fig. (1) and unilateral in the remaining [6] 50% of patients and this is in agree with Hamilton, T.W.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Out of the 12 patients diagnosed as avascular necrosis, the disease was bilateral in [6] 50% of patients Fig. (1) and unilateral in the remaining [6] 50% of patients and this is in agree with Hamilton, T.W.…”
Section: Discussionsupporting
confidence: 85%
“…Out of the 12 patients diagnosed as avascular necrosis, the disease was bilateral in [6] 50% of patients Fig. (1) and unilateral in the remaining [6] 50% of patients and this is in agree with Hamilton, T.W. et al [11] as they reported that it is important to evaluate the contralateral hip, as bilateral involvement has been reported to be between 40% and 80%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The succeeding case reports revealed that TOH may be bilateral [4][5][6][7][8][9][10][11][12] and that may affect not only the hip, but also other joints in the lower extremities, like knee or ankle [13][14][15]. Moreover, it soon became clear that cases were not restricted to pregnancy [16][17][18], or even to women, since the disease was also observed in men, usually in their fifties or sixties [19][20][21].…”
Section: Introductionmentioning
confidence: 97%